Is the expansion of universe accelerating or the Photons decelerating? - Tank, Hasmukh (International Journal of Advanced Astronomy, 2015)
Astronomical observations of the cosmological red-shift are currently interpreted in terms of â€˜expansion of universeâ€™ and â€˜accelerated-expansion of the universeâ€™, at the rate of H0 c; here H0 is Hubbleâ€™s constant, and c is the speed of light. Whereas a straight-forward derivation presented here suggests that: rather it is the photon which is decelerating, at the rate of H0 c. Such a deceleration of photons can be caused by virtual electrons, positrons and pi-mesons, contained in the extra galactic quantum vacuum, because: they do have gravitational-acceleration of the same order as H0 c at their â€œsurfacesâ€; or by decay of a photon into a lighter photon and a particle of mass h H0 / c2. Tired-light interpretations of the cosmological red-shiftâ€™ were so far considered as not compatible with the observations of â€˜time-dilation of super-novae light-curvesâ€™; so in a paper titled: â€œWave-theoretical insight into the relativistic â€˜length-contractionâ€™ and â€˜time-dilation of super-novae light-curvesâ€™â€ (Tank, Hasmukh K. 2013), it has been already shown that any mechanism which can cause â€˜cosmological red-shiftâ€™ will also cause â€˜time-dilation of super-novae light-curvesâ€™.Â Therefore, we now need not to remain confined to the Big-Bang model of cosmology.